Earth, Planets and Space - Ogawa, Yasuo
Earth, Planets and Space (EPS) covers scientific articles in Earth and Planetary Sciences, particularly geomagnetism, aeronomy, space science, seismology, volcanology, geodesy, and planetary science. EPS also welcomes articles in new and interdisciplinary subjects, including instrumentations. Only new and original contents will be accepted for publication. No review papers will be accepted.